INTERACTION BETWEEN LEGAL PROFESSIONALS AND FORENSIC EXPERT WITNESSES: PROBLEMS AND SOLUTIONS - S. Smirnova (Теория и практика судебной экспертизы)
The author uses case studies to illustrate various problems of interaction betweenindividual forensic examiners, forensic science organizations and judges at the stagesof preparation for the appointment of forensic examinations, as well as court hearingsand forensic expert witness testimony in court, and recommends possible solutions.